DETERMINATION OF MINERALS CONTENT IN LEAVES OF MORINGA OLEIFERA BY NEUTRON ACTIVATION ANALYSIS - Theresia Rina Mulyaningsih; Saeful Yusuf (Website, 2018)
DETERMINATION OF MINERALS CONTENT IN LEAVES OF MORINGA OLEIFERA BY NEUTRON ACTIVATION ANALYSIS. Moringa oleifera ( Mo) or kelor is a high-value plant, distributed in many tropical and subtropical countries. This plant can be used as a vegetable, cosmetic oil, and medicinal plant. The leaves of Mo is rich in essential minerals needed by the body’s health. Moringa oleifera widely cultivated in various places in Indonesia, easily obtained and inexpensive so precious can be used to overcome malnutrition. Research on the macro-micro mineral content in Moringa leaves here is still limited. Mineral composition in leaves include Mo leaves varies depending on location grow. The purpose of this research is to determine the mineral content in the leaves of the Mo taken from Indonesia. For the preliminary study samples was taken from Central Java to be compared with the results of studies conducted in several other countries. Leaf samples were collected randomly from sampling area. Mineral content in the samples is determined using Neutron Activation Analysis (NAA). Irradiation was carried out at Rabbyt System of Multipurpose Reactor G.A Siwabessy on neutron flux 1013n.cm-2.dt-1. The results obtained indicate that Mo is rich in essential minerals, mainly Ca, Mg, K, Zn, Fe and Cl. Content in dried leaves include: calcium (3.45 % ), magnesium ( 0.66 % ), potassium ( 3.35 % ), chloride (0,25%), iron (147.20 mg/kg), sodium ( 152.52 mg/kg ), zinc ( 35.71 mg / kg ), and manganese ( 102.10 mg/kg ) . Mo also contains other minerals such as chromium (4.76 mg/kg), bromine (4.82 mg/kg), cobalt (0.16 mg/kg), and aluminium (150.40 mg/kg) in addition to other element. Compared with the results of existing studies, it shows that mineral composition in Mo leaves varies depending on the location where the plant is grown.